Early detection of breast cancer – integrative review (Research, Society and Development, 2023)
Objective: To describe the most updated guidelines for early detection of breast cancer to investigate the main recommendations of the Ministry of Health based on evidence, and to describe the existing legislation and public policies for early detection of breast cancer. Method: Bibliographic research was conducted on articles related to health and nursing, with publications available online, indexed on the BVSALUD website, in the LILACS and Coleciona SUS (Brazil) databases, and in the Ministry of Health in Portuguese and Spanish languages from the last 5 years. The aim was to address early detection of breast cancer in Brazil and abroad. Results: Given the evident lack of knowledge about the disease among the population, primary health care services have become the best place to define good strategies aimed at raising awareness about the disease. Therefore, the need for Basic Health Units (UBS) to be composed of competent professionals to carry out educational and preventive actions, and to be prepared to identify suspected cases early and refer them to the reference service is emphasized. Conclusion: Achieving early screening and diagnosis can make a difference in a patient's prognosis and reduce mortality rates. However, the best techniques involve three factors combined: breast self-examination, clinical breast examination by a trained professional, and complementary exams such as mammography.